Implementation of Alternative Delivery Mode Learning Resources Amidst COVID-19 Pandemic: Basis for Intervention Program - R. Asio, John Mark; Jimenez, Edward (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
This study aimed to assess the implementation of the Alternative Delivery Mode (ADM) Learning Resources as a basis for an intervention program amidst the COVID-19 pandemic. The study employed a descriptive survey research design. Using a universal sampling technique, a total of 30 Learning Resource Coordinators in a selected school division in Central Luzon, Philippines participated in the survey and data gathering. The researchers also used an adapted research instrument to gather essential information for the study. With the help Microsoft Excel, the researchers tabulated and organized the data. Afterwards, the gathered data underwent descriptive statistical analysis using frequency and percentage. The study found that the ADM Learning Resources developed by teachers exceeded DepEd's total number of Most Essential Learning Competencies (MELCs). For the total number of learners who preferred modular printed learning modality, it reached 67.89%. There were 100% ADM Learning Resources provided to learners in all grade levels for the status of printed learning resources. Based on the earlier results, the researcher provided some essential recommendations, particularly an intervention program for this study.